Comparative Analysis of the Performance and Emissions Characteristics of a C.I. Engine Fuelled with Three Different Blends of Biodiesel Derived from Waste Mustard Oil - Vaneet (My University, 2012)
Decline in fossil fuel resources along with high crude oil prices generated attention towards the development of fuel from alternate sources. Such fuel should be economically attractive and performance competent in order to replace the fossil fuel. Biodiesel offer a very promising alternative to diesel oil since they are renewable and have similar properties. Throughout the world, there is an enormous amount of waste lipids generated from restaurants and food shops posing a challenge for their storage and proper disposal in the environment. Reuse of these oils not only helps in its management but also lowers the production cost of biodiesel. Biowaste cooking oils thus opened a good opportunity to study its suitability to produce biodiesel. Then, problem gets generated from viscosity of these biowaste cooking oils. Transesterification process was used to lower the viscosity of the waste oil. Biodiesel from waste mustard oil was prepared. The properties of B100 were studied. Then, Biodiesel was blended with petrodiesel at three different levels i.e. B10, B15 and B20 as the direct use may cease the engine. In this present research work, waste mustard biodiesel-diesel fuel blends as alternative fuels for diesel engines were studied. An experimental investigation has been carried out to evaluate the performance and emission characteristics of a diesel engine fuelled with waste mustard biodiesel and its blends (10%, 15% and 20%). The performance parameters analyzed include brake power, brake thermal efficiency, brake specific fuel consumption, and exhaust gas temperature whereas exhaust emissions include oxides of nitrogen, HC and CO. The results of the experiment in each case were compared with baseline data of diesel fuel. Significant improvements have been observed in the performance parameters of the engine as well as exhaust emissions. The waste mustard biodiesel-diesel fuel blends were tested in a single cylinder direct injection diesel engine. Engine performance and exhaust emission were measured at no, part and full load condition. This research investigates the scope of utilizing waste mustard oils as an alternative diesel fuel. An experimental investigation has been carried out to evaluate the performance and emission characteristics of a compression ignition engine fuelled with waste mustard biodiesel and important fuel properties have been determined. It concluded that B10 blend of waste mustard biodiesel act as best alternative fuel among all tested fuel at full load condition. The objective of the present research was to explore technical feasibility of waste mustard oil in direct injection CI engine without any substantial hardware modifications.
Master of Engineering (Thermal Engineering)
Keywords: Waste mustard oil; transesterification; performance; emission